Accuracy of European stock target prices - Joana Almeida; Raquel M. Gaspar (Journal of Risk and Financial Management, 2021)
Equity studies are conducted by professionals, who also provide buy/hold/sell recommendations to investors. Nowadays, target prices determined by financial analysts are publicly available to investors, who may decide to use them for investment purposes. Studying the accuracy of such analysts' forecasts is, thus, of paramount importance. Based upon empirical data on 50 of the biggest (larger capitalisation) European stocks over a 15-year period, from 2004 to 2019, and using a panel data approach, this is the first study looking at overall accuracy in European stock markets. We find that Bloomberg's 12-month consensus target prices have no predictive power over future market prices. Our panel results are robust to company fixed effects and subperiod analysis. These results are in line with the (mostly US-based) evidence in the literature. Extending common practice, we perform a comparative accuracy analysis, comparing the accuracy of target prices with that of simple capitalisations of current prices. It turns out target prices are not better at forecasting than simple capitalisations. When considering individual regressions, accuracy is still very low, but it varies considerably across stocks. By also analysing the relationship between both measures-target prices and capitalised prices-we find evidence that, for some stocks, capitalised prices partially explain how target prices are determined.
Keywords: 330; forecast accuracy; panel data analysis; target prices